Kepatuhan Wajib Pajak Kendaraan Bermotor di Kantor Samsat Denpasar - Rambu Hunggu Hau Maritu; Anik Yuesti; Putu Novia Hapsari Ardianti (Jurnal Inovasi Akuntansi (JIA), 2023)
Taxpayer compliance is an act that reflects obedience and awareness of order in the taxpayer's tax obligations by making payments and reporting on the period and yearly of the taxpayer concerned in accordance with applicable tax provisions. Increasing taxpayer compliance is influenced by many factors, such as tax audits carried out, sanctions given to each taxpayer who violates the regulations, awareness of the taxpayer himself, quality of service provided to taxpayers, and knowledge of taxation owned by each taxpayer. The number of samples used in this study were 100 respondents. The sampling technique used in this research is incidental sampling. The data analysis technique used is Multiple Linear Regression analysis and previously tested research instruments. The results of this study indicate that service quality has a positive effect on motor vehicle taxpayer compliance at the Denpasar Samsat Office, on the other hand tax audits, tax sanctions, taxpayer awareness and tax knowledge do not affect taxpayer compliance. These results indicate that the Denpasar Samsat Office has good service quality where taxpayers feel comfortable and satisfied with the services provided so that it can affect the level of taxpayer compliance.